(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
Ethics committee activity is strictly embedded in the development and implementation of clinical research: from the most regulated clinical trials on medicines, to retrospective observational studies without medicines, with lower clinical risk for involved subjects, but with potential risks for data protection and quality of evidence dumped in the scientific literature. The application of the 536/14 regulation aims to accelerate authorisation of clinical trials on medicines, by requiring the assessment by only one Ethics Committee per Country and tight deadlines. Strict monitoring of these studies during their implementation is needed, with the aim to verify the actual compliance with the main principles of clinical research.